2018
DOI: 10.1111/cns.12996
|View full text |Cite
|
Sign up to set email alerts
|

De‐palmitoylation by N‐(tert‐Butyl) hydroxylamine inhibits AMPAR‐mediated synaptic transmission via affecting receptor distribution in postsynaptic densities

Abstract: Our data suggest that the palmitoylation-deficient state initiated by NtBuHA preferentially reduces AMPAR function, which may potentially be used for the treatment of CNS disorders, especially infantile neuronal ceroid lipofuscinosis (Batten disease).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…We here demonstrated that blocking neuronal activity with TTX to simulate increased transmission strength in synaptic network enhanced the global palmitoylation and PSD-95 and glutamate receptor palmitoylation levels, as well as the synaptic and membrane surface distribution of these PSD proteins. Consistent with our previous results (Shen et al, 2019;Xia et al, 2019), treating with palmitoylation inhibitors, 2-BP or NtBuHA, reversed the increased palmitoylation levels or synaptic expression of the target molecules, such as PSD-95, GluA1-2, and NMDARs. Additionally, depalmitoylation plays a pivotal role in recycling and/or degradation of proteins that undergo palmitoylation (Greaves and Chamberlain, 2007;Salaun et al, 2010); and in clinical research, analysis of the brains of patients with infantile neuronal ceroid lipofuscinosis compared with control samples revealed an obvious deficiency of PPT1, which impairs the cleavage of thioester linkage in palmitoylated proteins, and prevents the degradation and causes accumulation of lysosomal ceroid (Kim et al, 2008;Sarkar et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…We here demonstrated that blocking neuronal activity with TTX to simulate increased transmission strength in synaptic network enhanced the global palmitoylation and PSD-95 and glutamate receptor palmitoylation levels, as well as the synaptic and membrane surface distribution of these PSD proteins. Consistent with our previous results (Shen et al, 2019;Xia et al, 2019), treating with palmitoylation inhibitors, 2-BP or NtBuHA, reversed the increased palmitoylation levels or synaptic expression of the target molecules, such as PSD-95, GluA1-2, and NMDARs. Additionally, depalmitoylation plays a pivotal role in recycling and/or degradation of proteins that undergo palmitoylation (Greaves and Chamberlain, 2007;Salaun et al, 2010); and in clinical research, analysis of the brains of patients with infantile neuronal ceroid lipofuscinosis compared with control samples revealed an obvious deficiency of PPT1, which impairs the cleavage of thioester linkage in palmitoylated proteins, and prevents the degradation and causes accumulation of lysosomal ceroid (Kim et al, 2008;Sarkar et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, for some membrane receptors that are known to be palmitoylated, no evidence was reported until now for a role of palmitoylation on receptor signalization or trafficking. This is the case for instance of α-AR (Kennedy and Limbird, 1993) and NMDAR (Xia et al, 2019).…”
Section: Discussionmentioning
confidence: 96%
“…Namely, the study by Xia et al , used an acute (30 minute) NtBuHA incubation and made physiological recordings of spontaneous postsynaptic events, which are AMPA receptor mediated, whereas we used a chronic treatment paradigm and imaged postsynaptic calcium transients, which involve both calcium permeable AMPA receptors and NMDA receptors [28,29]. These are crucial differences, considering Xia and colleagues noted a reduction in AMPA, but not NMDA receptor palmitoylation following acute NtBuHA treatment [48], while our previous data show that chronic palmitoylation inhibitor treatment can impact NMDA receptor palmitoylation [28]. Furthermore, we studied NtBuHA effects in Cln1 −/− neurons, which demonstrate dysregulation of both glutamate receptor subtypes [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Here, we demonstrate that chronic supplementation of NtBuHA in the medium of Cln1 -/primary cortical neurons corrected the increased frequency of postsynaptic calcium transients compared to untreated Cln1 -/neurons. Supporting this finding, recent work [48] shows that NtBuHA treatment impacts AMPA receptor transmission in hippocampal slices, although the effect was a reduction in the amplitude, rather than the frequency, of spontaneous postsynaptic events [48]. This discrepancy is reconciled by methodological differences.…”
Section: Potential Mechanisms For Reduction Of Seizure With Ntbuha Tr...mentioning
confidence: 95%
See 1 more Smart Citation